Social Media Marketing For Dummies, 4th Edition - Singh, Shiv; Diamond, Stephanie (--For dummies., 2020)
Make friends and sell things to people through social media Social media technology is restlessly inventive, providing thousands of awesome ways for you to market your business inexpensively and on a large scale-often directly into the pockets of consumers. But in the proliferating, ever-changing world of tweets, influencers, handles, and alerts, it can be hard to know where to begin and then to evaluate what's actually working for you. In the new edition of Social Media Marketing for Dummies , leading SMM voices Shiv Singh and Stephanie Diamond clear away the confusion and show you the smartest, most effective ways to plan, launch, manage, and assess your campaigns-and then iterate and optimize for increased success. Incorporating the latest trends and presented in a friendly, easily digestible step-by-step style, you'll find the ultimate blueprint for developing your best SMM strategy. In no time, you'll find out how to line up with Facebook, Twitter, Tumblr, and Google, develop a unique and compelling voice, and influence your key audience all the way to the bank. Choose the best SMM combination for you Avoid common mistakes and pitfalls Track your customers from awareness to retention Try out the latest stuff that really works Whether your organization is large or small, it simply doesn't pay to be shy. Find your voice, get social, and chat your way to attracting and keeping new customers today!